Immobilization of confined European bison with a medetomidine - zolazepam/tiletamine - butorphanol combination using readily available veterinary medicinal products (European Bison Conservation Newsletter, 2022)
Various protocols have been used to immobilize European bison in recent years. Nevertheless, availability, human toxicity, animal side effects, costs and legal obstacles continue to cause problems for breeders of the European Bison. We have therefore applied an immobilization protocol that is essentially based on medetomidine, zolazepam/tiletamine and butorphanol using products, which are readily available on the market. The basic prerequisite for the application is the ability to separate individual animals and apply larger volumes using a jab stick. This paper shows the results of 21 immobilizations of animals that were intended for transport to other breeding enclosures or for reintroduction projects between 2019 and 2021. The combination is suitable for most immobilization reasons and meets all requirements for safe and animal-friendly immobilization.
Keywords: European bison; immobilization; medetomidine; zolazepam/tiletamine; butorphanol; jab stick